Comprehensive Analysis of Human microRNA–mRNA Interactome - Plotnikova, Olga; Baranova, Ancha; Skoblov, Mikhail (Frontiers in Genetics, 2019)
MicroRNAs play a key role in the regulation of gene expression. A majority of microRNA-mRNA interactions remain unidentified. Despite extensive research, our ability to predict human microRNA-mRNA interactions using computational algorithms remains limited by a complexity of the models for non-canonical interactions, and an abundance of false positive results. Here we present the landscape of human microRNA-mRNA interactions derived from comprehensive analysis of HEK293 and Huh7.5 datasets, along with publicly available microRNA and mRNA expression data. We show that while only 1-2% of human genes were the most regulated by microRNAs, few cell line- specific RNAs, including EEF1A1 and HSPA1B in HEK293 and AFP, APOB and MALAT1 genes in Huh7.5, display substantial “sponge-like” properties. We revealed a group of microRNAs that are expressed at a very high level, while interacting with only a few mRNAs, which, indeed, serve as their specific expression regulators. In order to establish reliable microRNA binding regions, we collected and systematically analyzed the data from 79 CLIP datasets of microRNA binding sites. We report 46,805 experimentally confirmed mRNA-miRNA duplex regions. Resulting dataset is available at http://score.generesearch.ru/services/mirna/. Our study provides initial insight into the complexity of human microRNA-mRNA interactions.